Transcriptional control of hydrogen peroxide homeostasis regulates ground tissue patterning in the Arabidopsis root - Oh, Jiyeong; Choi, Ji Won; Jang, Sejeong; Kim, Seung Woo; Heo, Jung-Ok; Yoon, Eun Kyung; Kim, Soo-Hwan; Lim, Jun (Frontiers in Plant Science, 2023)
In multicellular organisms, including higher plants, asymmetric cell divisions (ACDs) play a crucial role in generating distinct cell types. The Arabidopsis root ground tissue initially has two layers: endodermis (inside) and cortex (outside). In the mature embryo, the endodermis undergoes additional ACDs to produce the endodermis itself and the middle cortex (MC), located between the endodermis and the pre-existing cortex. In the Arabidopsis root, gibberellic acid (GA) deficiency and hydrogen peroxide (H2O2) precociously induced more frequent ACDs in the endodermis for MC formation. Thus, these findings suggest that GA and H2O2 play roles in regulating the timing and extent of MC formation. However, details of the molecular interaction between GA signaling and H2O2 homeostasis remain elusive. In this study, we identified the PEROXIDASE 34 (PRX34) gene, which encodes a class III peroxidase, as a molecular link to elucidate the interconnected regulatory network involved in H2O2-and GA-mediated MC formation. Under normal conditions, prx34 showed a reduced frequency of MC formation, whereas the occurrence of MC in prx34 was restored to nearly WT levels in the presence of H2O2. Our results suggest that PRX34 plays a role in H2O2-mediated MC production. Our findings suggested that PRX34 plays a role in H2O2-mediated MC production. Furthermore, we provide evidence that SCARECROW-LIKE 3 (SCL3) regulates H2O2 homeostasis by controlling transcription of PRX34 during root ground tissue maturation. Taken together, our findings provide new insights into how H2O2 homeostasis is achieved by SCL3 to ensure correct radial tissue patterning in the Arabidopsis root.